Physiological effects of formulation containing tannase-converted green tea extract on skin care: physical stability, collagenase, elastase, and tyrosinase activities - Yang-Hee Hong; Eun Young Jung; Dong Ouk Noh; Hyung Joo Suh (Integrative Medicine Research)
Background: Green tea contains numerous polyphenols, which have health-promoting effects. The purpose of this study was to evaluate the effect of tannase-converted green tea extract (TGE) formulation on the physical stability and activities of skin-related enzymes. Methods: Physical stability was evaluated by measuring the pH, precipitation, and colors at 25 ± 2 °C/ambient humidity and at 40 ± 2 °C/70% ± 5% relative humidity for 4 months. Activities of collagenase, elastase, and tyrosinase as skin-related enzymes were assessed on TGE formulation. Results: The concentrations of epigallocatechin-3-gallate and epicatechin-3-gallate in green tea extract were greatly decreased to the extent of negligible level when treated with tannase. The formulation containing 5% tannase-converted green tea extract showed relatively stable pH, precipitation, and color features for 16 weeks. When TGE was added to the formulation, there was a significant increase in the inhibition of elastase and tyrosinase activities (p < 0.05) compared with the formulation containing 5% normal green tea extract. Conclusion: The TGE could be used in cosmetics as skin antiwrinkling or depigmenting agent.